1
$\begingroup$

Given $\sum a_n$ and $\sum b_n$ we define the Cauchy product to be $\sum c_n$ , where $c_n=\sum_{k = 0}^{n}a_kb_{n-k}$. It is well known that for $a_n,b_n \in \mathbb{R}$, if $\sum a_n$, $\sum b_n$ and $\sum c_n$ converges, then $\sum c_n=\sum a_n\sum b_n$. Is it true when $a_n,b_n \in \mathbb{C}$?

Thanks in advance!

$\endgroup$
  • 2
    $\begingroup$ Yes, it can be proved the same way. $\endgroup$ – Lord Shark the Unknown May 8 '18 at 3:33
  • $\begingroup$ Typically: look at the proof, see if anything breaks. More likely than not, nothing will. $\endgroup$ – Clement C. May 8 '18 at 3:33
  • $\begingroup$ @Lord Shark the Unknown Thanks for your answer! What is the same way? Is it to use abel’s theorem? $\endgroup$ – 04170706 May 8 '18 at 3:35
  • $\begingroup$ Abel's theorem works fine @0706 $\endgroup$ – Lord Shark the Unknown May 8 '18 at 3:38
  • $\begingroup$ How to solve in a more basic way? $\endgroup$ – XT Chen Apr 15 at 6:51
1
$\begingroup$

Abel's Lemma. If $\{a_n\}\subset\mathbb R$ and $\sum a_n$ converges, then $\lim_{x\to 1^-}\sum_{n=0}^\infty a_nx^n=\sum_{n=0}^\infty a_n$.

Clearly, Abel's Lemma holds even if $\{a_n\}\subset\mathbb C$, as we can write $a_n=\mu_n+i\nu_n$ and apply the lemma for the two real sequences $\{\mu_n\}$ and $\{\nu_n\}$.

Next we need the following lemma:

Lemma. If the complex series $\sum a_n$ and $\sum b_n$ converge absolutely, then so does their convolution $c_n=a_0b_n+\cdots+a_nb_0$ and $\sum_{n=0}^\infty c_n=\sum_{n=0}^\infty a_n\sum_{n=0}^\infty b_n$.

In our case, since $\sum a_n$ and $\sum b_n$ converge, then the power series $\sum_{n=0}^\infty a_nz^n$ and $\sum_{n=0}^\infty b_nz^n$ have radius of convergence $R\ge 1$, and hence $\sum_{n=0}^\infty c_nz^n$ converges and $\sum_{n=0}^\infty c_nz^n=\Big(\sum_{n=0}^\infty a_nz^n\Big)\Big(\sum_{n=0}^\infty b_nz^n\Big)$, for all $|z|<1$.

Now, using Abel's Lemma (complex version) we have that $$ \sum_{n=0}^\infty c_n=\lim_{x\to 1^-} \sum_{n=0}^\infty c_nx^n =\lim_{x\to 1^-}\big(\sum_{n=0}^\infty a_nx^n\Big)\big(\sum_{n=0}^\infty b_nx^n\Big)= \big(\sum_{n=0}^\infty a_n\Big)\big(\sum_{n=0}^\infty b_n\Big). $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.